Women-led CBBPs Placed under the supervision of Universities and Research Centers - Belay, Berhanu; Getachew, Tesfaye; Haile, Aynalem (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
CBBP is a participatory genetic improvement program that considers household settings, including women and children. Family members, particularly women, have a significant role in small ruminant management, which has necessitated the initiation of women-led CBBPs. Women-led CBBP is characterized by the women (Married or widowed) as focal persons to receive training, participate in CBBP, consult, be members of the cooperatives, and be active in CBBP cooperative leadership. In organizing women-led CBBP, couple training is chosen to disseminate agricultural technologies in a rural setting. A couple of training sessions involve a wife and husband to orient the purposes of women-led CBBP, and later on, the women become the focal person to receive training and run the routines of CBBP. In doing so, the household heads, men, are convinced to allow any CBBP activity to be channeled through women. Women run the CBBP cooperatives and range from membership to leadership. The partnership among ICARDA, research centers, and universities has yielded seven women-led and existing CBBPs with 486 active members in 2022 and three new ones with 147 members under the support of ICARDA and partners. In sum, Initiating women-led CBBP requires a series of consultations that need to be conducted to benefit from women's engagement in small ruminant improvement. Capacity building in smart-pack value addition, such as the fattening, needs to be strengthened to use the versatility of women in small ruminant management.